Delineation of critical amino acids in activation function 1 of progesterone receptor for recruitment of transcription coregulators - Woo, Amanda Rui En (2020)
The activation functions AF1 and AF2 of nuclear receptors mediate the recruitment of coregulators in gene regulation. AF1 is mapped to the highly variable and intrinsically unstructured N terminal domain and AF2 lies in the conserved ligand binding domain. The unstructured nature of AF1 offers structural plasticity and hence functional versatility in gene regulation. However, little is known about the key functional residues of AF1 that mediates its interaction with coregulators. This study focuses on the progesterone receptor (PR) and reports the identification of K464, K481 and R492 (KKR) as the key functional residues of PR AF1. The KKR are monomethylated and function cooperatively. The combined mutations of KKR to QQQ render PR isoform B (PRB) hyperactive, whereas KKR to FFF mutations abolishes as much as 80% of PR activity. Furthermore, the hyperactive QQQ mutation rescues the loss of PR activity due to E911A mutation in AF2. The study also finds that the magnitudes of the mutational effect differ in different cell types as a result of differential effects on the functional interaction with coregulators. Furthermore, KKR provides the interface for AF1 to physically interact with p300 and SRC-1, and with AF2 at E911. Intriguingly, the inactive FFF mutant interacts strikingly stronger with both SRC-1 and AF2 than wt PRB. We propose a tripartite model to describe the dynamic interactions between AF1, AF2 and SRC-1 with KKR of AF1 and E911 of AF2 as the interface. An overly stable interaction would hamper the dynamics of disassembly of the receptor complex.